For an institutional evaluation system in Brazilian professional education - Peixoto, Nirvan Hofstadler; Silveira, Juliane Vanessa Rippel; Barroso, Lidiane Bittencourt (Seven Editora, 2023)
A nation must plan the future of its education, seeking to provide a more quality education for its people. In Brazil, the evaluation of professional education is not inserted in the context of the evaluations undertaken by the country. This demonstrates the State's lack of interest in materializing an institutional evaluation system for this level of education. In the globalized context of today's society, the exaggerated growth of capitalism and economic scarcity interfere with the course of professional education institutions, bearing in mind the values and mission of professional education are substantial so that the essence of the function of professional education is not forgotten. This paper sought to discuss the importance of developing a system of evaluation of professional education, considering the human right to quality education with the democratization of education. The investigation is justified in the social function of institutional evaluation, because in addition to being a fruitful tool in the consolidation of the priorities established in the educational plans, the institutional evaluation can be seen as a tool capable of ensuring transparency to the actions of educational institutions, and the results obtained can be seen as accountability of the institutions to society.  It is concluded that the elaboration of a system of evaluation of professional education goes beyond the evaluation of knowledge related to a particular craft, and has the purpose of verifying if the professional training is consistent with the requirements and professional profiles and if the educational services offered are effective and that promote, in fact, effective learning.DOI:https://doi.org/10.56238/alookdevelopv1-088